Answer:
0 to 2 minutes - Accelerating
3 to 4 minutes - Constant
6 to 8 minutes - Decelerating
9 to 11 minutes Accelerating
hope i have helped u
Step-by-step explanation:
Hello,
(x-(-1+4i))(x-(-1-4i))=((x+1)-4i)((x+1+4i)
=((x+1)²+16
=x²+2x+17
Answer:
y=-1/8y+1
Step-by-step explanation:
flip the equation, then add -8 to both sides to cancel out the +8 on the left, then divide sides by -8Let's solve for x.
y=−8x+8
Step 1: Flip the equation.
−8x+8=y
Step 2: Add -8 to both sides.
−8x+8+−8=y+−8
−8x=y−8
Step 3: Divide both sides by -8.
The answer is 14 my name is freind45
Answer:
3.3166
Step-by-step explanation:
use calc